2020
DOI: 10.1016/j.athoracsur.2020.02.079
|View full text |Cite
|
Sign up to set email alerts
|

Distal Stent Graft–Induced New Entry After TEVAR or FET: Insights Into a New Disease From EuREC

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 27 publications
0
30
0
3
Order By: Relevance
“…Deliberate deployment of the distal stent-graft in the descending aorta above the level of the aortic valve should be considered to prevent spinal cord complications. 18 There have been some reports regarding the occurrence of stent-graft-induced new entry, 25 but we found that its incidence using the Frozenix was quite low because the Frozenix has an internal stent skeleton. The occurrence of stent-graft-induced new entry can be alleviated by inserting the FET in a vertical position.…”
Section: Discussionmentioning
confidence: 71%
“…Deliberate deployment of the distal stent-graft in the descending aorta above the level of the aortic valve should be considered to prevent spinal cord complications. 18 There have been some reports regarding the occurrence of stent-graft-induced new entry, 25 but we found that its incidence using the Frozenix was quite low because the Frozenix has an internal stent skeleton. The occurrence of stent-graft-induced new entry can be alleviated by inserting the FET in a vertical position.…”
Section: Discussionmentioning
confidence: 71%
“…This experience also shows the importance of lifelong surveillance after open or endovascular TAAA repair, especially in patients with dissection and in those with connective tissue disorders. Indeed, TEVAR for dissection carries a risk for stent-graft induced new entry tears, which, in turn, may warrant further re-intervention, 15,16 and regular lifelong imaging controls are, therefore, warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Ein ähnlicher Mechanismus lässt sich beobachten, wenn nach TEVAR die Dissektionsmembran am distalen Stentgraftende durch zu hohe Scherkräfte (meist bei überdimensioniertem Stentgraft) nach innen ins falsche Lumen einreißt. Hier spricht man dann von einem "distal stent-graft induced new entry" (dSINE) [9,24].…”
Section: Zahl Und Größe Der Kommunikationen Zwischen Den Luminaunclassified
“…Hierbei weist die Lokalisation des primären Entrys in angulierten Aortensegmenten (Aortenbogen, proximale Aorta descendens) eine stärkere Korrelation mit dem Auftreten von Malperfusion auf [2 -5].Mechanismen für eine AneurysmaformationDer Hauptgrund der Aneurysmaformation liegt im Blutdruckunterschied zwischen wahrem und falschem Lumen und im Winkel, in dem der Blutstrom auf die Aortenwand auftrifft. Diese Faktoren werden wiederum durch die Lokalisation des primären Entrys und auch durch die Zahl und Größe der Kommunikationen zwischen den beiden Lumina (vormals auch als multiple Entrys und Reentrys bezeichnet) bestimmt.Ein weiterer wesentlicher Faktor ist die Größe der distalsten Kommunikation zwischen den Lumina oder auch der distalste Einriss (Reentry), dabei kleinem oder fehlendem Reentryder mittlere arterielle Blutdruck im falschen Lumen deutlich höher sein kann als im wahren Lumen und es dadurch zu einer peripheren Widerstandserhöhung kommt[9,10].FALLBEISPIEL 1 Akute komplizierte Typ-B-Dissektion Klinisches Szenario Ein 57 Jahre alter Mann erleidet plötzlichen akuten Thoraxschmerz, der zwischen den Schulterblättern beginnt und wandernd bis in die Leiste ausstrahlt. Nach 5 Minuten entwickelt er zunächst Sensibilitätsstörungen, danach eine Paraparese und letztlich eine Paraplegie der rechten unteren Extremität.…”
unclassified